Biochemical characterization of wheat straw cell wall with special reference to bioactive profile. Issue 1 (1st January 2018) - Tufail, Tabussam; Saeed, Farhan; Imran, Muhammad; Arshad, Muhammad Umair; Anjum, Faqir Muhammad; Afzaal, Muhammad; Bader Ul Ain, Huma; Shahbaz, Muhammad; Gondal, Tanweer Aslam; Hussain, Shahzad
ABSTRACT: The core objective of the current study was to extract and characterize the wheat straw cell wall for its nutritional and bioactive profile. For the purpose, four different wheat straw varieties namely Ujala-16, Johar-16, Gold-16, and Galaxy-13 were procured from Ayub Agriculture Research Institute, Faisalabad, Pakistan. The whole research was conducted in three different phases. In first phase, nutritional composition and mineral profile of straw of different wheat varieties were determined. In second phase, wheat straw cell wall of different varieties was isolated and characterized for its important bioactive constituents, such as lignin, cellulose, hemicelluloses, phytosterol, and policosanol (PC) content. Results showed that straw of different wheat varieties contained 7.75–9.24, 3.98–5.06, 3.43–3.98, and 1.60–2.24 g/100 g moisture, ash, protein, and fat contents, respectively, whereas potassium, calcium, phosphorus, and magnesium were 1.19–2.03, 0.10–0.79, 0.10–0.98, 0.03–0.98 ppm, respectively. Moreover, lignocellulosic mass: cellulose 37.75–38.18 g/100 g raw material, lignin 15.67–16.07 g/100 g raw material, hemicelluloses 28.25–28.98 g/100 g raw material, was present in wheat straw and varied significantly among different varieties. In addition, phytosterol ranged from 854 to 1176 mg/kg in straw of different wheat cultivars, whilst PC from 196.09 to 236.48 mg/kg. Conclusively, wheat straw was an excellent source of many important bioactive moieties especially lignocelluloses and could have functional use.